2004
DOI: 10.1002/dmrr.424
|View full text |Cite
|
Sign up to set email alerts
|

A linkage study of 12 IDDM susceptibility loci in the Finnish population

Abstract: Our results are consistent with previous findings of linkage or association to T1D at IDDM2, IDDM6, IDDM9, IDDM12 and 12q12-q15 regions but do not unambiguously confirm them. A larger sample set is required to gain statistical power needed to confirm our findings in the Finnish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Though multiple genes are implicated as disease susceptibility markers in T1DM [1], the major genes responsible for at least 50% of the T1DM genetic component are human leukocyte antigen (HLA) linked [2]. DQB1 * 0201, DQB1 * 0302, DRB1 * 03 and DRB1 * 04 alleles confer susceptibility to T1DM, but the highest genetic risk is conferred by specific class II haplotypes rather than by particular alleles [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Though multiple genes are implicated as disease susceptibility markers in T1DM [1], the major genes responsible for at least 50% of the T1DM genetic component are human leukocyte antigen (HLA) linked [2]. DQB1 * 0201, DQB1 * 0302, DRB1 * 03 and DRB1 * 04 alleles confer susceptibility to T1DM, but the highest genetic risk is conferred by specific class II haplotypes rather than by particular alleles [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike T1D where the MHC region of chromosome 6 accounts for approximately 40% of the genetic risk of the disease in concert with other genes [25], and in T2D where genome-wide association studies have identified approximately 50 genetic loci associated with T2D in lean and obese individuals [26][27][28], there are no distinct genes that are unique to double diabetes. However, it is believed that the major genes that are independently associated with susceptibility to either T1D (e.g., the MHC and cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) [29] or T2D (e.g., the genes encoding adiponectin (APM1) and transcription factor 7-like 2 (TCF7L2) [30] can serve as genetic determinants for double diabetes, such that the frequency of the major T1D genetic susceptibility gene (MHC) is reduced, whereas the expression of the genes associated with T2D is enhanced [31].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Susceptibility to T1DM is conferred by multiple genes [8], among which the human leukocyte antigen (HLA) region has the strongest influence [9]. Some studies have demonstrated that HLA‐susceptible T1DM genotypes are important determinants of earlier disease onset, and that young age at diagnosis [10,11] and HLA susceptible genotypes are associated with lower C‐peptide levels at diagnosis [11].…”
Section: Introductionmentioning
confidence: 99%